Remeasuring man. Issue 3 (25th April 2014) - Weisberg, Michael
SUMMARY Samuel George Morton (1799–1851) was the most highly regarded American scientist of the early and middle 19th century. Thanks largely to Stephen Jay Gould's book The Mismeasure of Man, Morton's cranial capacity measurements of different races is now held up as a prime example of and cautionary tale against scientific racism. A team of anthropologists recently reevaluated Morton's work and argued that it was Gould, not Morton, who was biased in his analysis. This article is a reexamination of the Morton and Gould controversy. It argues that most of Gould's arguments against Morton are sound. Although Gould made some errors and overstated his case in a number of places, he provided prima facia evidence, as yet unrefuted, that Morton did indeed mismeasure his skulls in ways that conformed to 19th century racial biases. Gould's critique of Morton ought to remain as an illustration of implicit bias in science.